(untitled) (Swiss Medical Weekly, 2011)
Biomarkers are indicators of biological conditions that can be detected and measured in body fluids or tissues. Biomarkers can be detectable before the clinical onset of the disease, and are thus useful for prognosis; they can be measured at early stages of the disease and are useful for stratification and classification of the disease and patients; they can be monitored along the disease course and used as indicators of risk factors and pharmacological response to treatment. Ideally, biomarkers should be sensitive, specific, have high predictive power, and be easily accessible. Rheumatoid arthritis (RA) is the most frequent chronic inflammatory disorder, affecting millions of people worldwide and leading to joint damage and substantial morbidity. RA is a heterogeneous disorder with a fluctuating clinical course and unpredictable prognosis. And although a large panel of biologics is available to clinicians, the main challenge remains to treat patients as early as possible with the most personalised therapy. Today, the most challenging issue in RA is the identification of biomarkers for early disease diagnosis and for prediction of drug response. Among molecules that can fulfil this expectation, micro(mi)-RNAs certainly represent an option. The potential value of miRNAs as a novel class of biomarkers is well documented in cancer. Moreover, the presence and stability of miRNAs in body fluids provide fingerprints that can serve as molecular biomarkers for disease diagnosis and therapeutic outcome. As a growing body of evidences reveals abnormal expression of specific miRNAs in RA tissues, the use of a blood-based miRNA signature for optimal diagnosis and treatment becomes a realistic option.